How to Help Your Child Read - Corliss, William S. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This guide is divided into seven main sections. "How to Help Your Child Read" discusses the importance of being aware of your child, your schools, school-related factors, particular ways of helping your child in reading, and yourself. The Unit: "Help Me Help My Child" discusses assignment of pupil to teacher, grouping procedures, size of groups, reading consultant, remedial reading program, summer school, summer library program, and special personnel. "Organizational Patterns" discusses the Joplin Plan, team teaching, cooperative teaching, ungraded primary and self-contained classroom grouping. The "Materials" section discusses quality of authorship and content, basic materials, and supplementary programs. "Objectives of Reading" discusses the school's responsibility regarding initial reading experiences, development of skills, and reading attitude. "Reading Comprehension" discusses oral language interpretation and evaluation of reading. "Reading Word Attack Skills" discusses the basic skills necessary in a sound reading program, such as phonics, visual and auditory discrimination, vocabulary, etc. (WR)
ERIC Note: Unpublished manuscript.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beginning Reading; Classification; Parent Education; Parent School Relationship; Reading; Reading Achievement; Reading Comprehension; Reading Improvement; Reading Instruction; Reading Materials; Reading Programs; Reading Readiness; Reading Skills